2006
DOI: 10.4038/jas.v2i1.8112
|View full text |Cite
|
Sign up to set email alerts
|

Productivity and soil fertility status as influenced by integrated use of n-fixing biofertilizers, organic manures and inorganic fertilizers in onion

Abstract: One of the major constraints associated with onion (Allium cepa L.) cultivation is improper nutrient management. This necessitates to ascertain an efficient and economical integrated approach with renewable source such as organic manure and biofertilizers. In this context a field experiment was carried out at Acharya N.G.Ranga Agricultural university, Hyderabad, India to study the productivity and soil fertility status as influenced by integrated nutrient management in onion using cv. N-53. The twelve treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 2 publications
4
32
0
Order By: Relevance
“…Due to continuous inorganic fertilizers consumption results in micronutrients deficiency, disproportion in physiochemical properties of soil and low production of crops. For that reason these minerals are applied as affliction foliar form (Jeyathilake et al 2006). Foliar application of nutrients at proper growth phases is essential for their consumption and improved crop performance (Anadhakrishnaveni et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Due to continuous inorganic fertilizers consumption results in micronutrients deficiency, disproportion in physiochemical properties of soil and low production of crops. For that reason these minerals are applied as affliction foliar form (Jeyathilake et al 2006). Foliar application of nutrients at proper growth phases is essential for their consumption and improved crop performance (Anadhakrishnaveni et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The superiority expressed by the wider spacing over the closely spaced was in accordance with the findings of Colla et al (2002) on onion. In addition Jeyathilake et al (2006) confirmed that closer spacing results in the growth of less vigorous plant when compared with wider spacing. The results of onion spacing experiment reported by Khan et al (2002) showed that not only were the leaves of onion more from wider spacing but they had thicker and larger leaves.…”
Section: Discussionmentioning
confidence: 54%
“…This distinct response of potato yield and its components to graded rates of enriched compost emphasized its essential role in establishment of fertile media for growing potato plants leading to healthy vegetative growth and consequently sustain these plants to give high quality and quantity of potato yield. The prominent role of organic materials in enhancement of plant productivity was proved by many investigators (Jayathilake et al, 2006;Abdel-Wahab, 2008 andEl-Saiid, 2011).…”
Section: Potato Yield and Its Componentsmentioning
confidence: 95%